The Oil Must Flow at Any Cost: Catastrophic Aquatic Contamination and Literary Eco-Activism in Imbolo Mbue’s How Beautiful We Were and Chinelo Okparanta’s Short Story “America” - Badmus, Aminat Emma (Linguæ & - Journal of Modern Languages and Cultures, 2025)
Water is crucial for the survival of living organisms, especially humans. Yet despite its relevance, there are still billions of people around the world who lack access to clean water for drinking, cooking and sanitation purposes. The United Nations Global Water Security Assessment of 2023 revealed that thirteen African countries are currently facing a severe water crisis. This crisis not only affects the availability of safe drinking water but also has far-reaching consequences for public health, agriculture, economic development and social stability of affected regions. The West African region, in particular, has long been plagued by water contamination, with the exploration and production of crude oil among the most significant contributors to environmental degradation. This pollution has led to the de-naturalisation of the natural environment, posing a significant threat to the aquatic ecosystem, which, in turn, affects the livelihoods of millions of people in sub-Saharan Africa. In response to the ecological crisis gripping sub-Saharan African populations, modern women writers are employing their writings to sensitise their readers and promote a moral responsibility towards implementing practical and sustainable ways of reversing the increasing and rapid pollution of water resources. Building upon these premises and broadening the concept of eco-activism introduced by Egya (2020), this study investigates the ways in which How Beautiful We Were (2021) by Imbolo Mbue and the short story “America” (2013) by Chinelo Okparanta depict the impacts of human endeavours on the natural aquatic ecosystem. In these terms, specific attention will be directed to the analysis of the use of water imagery by both authors to channel the indecipherable and invisible nature of the structural violence that oil industries perpetuate on sub-Saharan African territory, together with the devastating physical and psychological effects of human activity on people living in polluted environments.